Conceptual strategies for a training program for teachers of Regular Basic Education about sexual identity with a focus on Personalistic Bioethics - Aguilar Valdiviezo, Irene Consuelo (2018)
The knowledge of the sexual identity conformation of the human person, has become an important factor in the integral formation of teachers of all areas and levels of Regular Basic Education due to the policies on integral sexual education that have been introduced in the new national curriculum with a focus on gender equality. Therefore, this communication aims to address the theoretical basis of sexual identity and then give way to conceptual strategies that will allow, subsequently, to consolidate the proposal of a training with a personalist bioethical approach. These guidelines highlight, albeit briefly, the contents that will be addressed in the program, taking into account that, with these topics, teachers can acquire the necessary skills to contribute to the consolidation of the sexual identity of their students, where the uniqueness of the human person is highlighted as a man or as a woman.